Enzymatic Epoxidation of Long-Chain Terminal Alkenes by Fungal Peroxygenases - Babot, Esteban D.; Aranda, Carmen; Kiebist, Jan; Scheibner, Katrin; Ullrich, René; Hofrichter, Martin; Martínez, Angel T.; Gutiérrez, Ana (Antioxidants, 2022)
Terminal alkenes are among the most attractive starting materials for the synthesis of epoxides, which are essential and versatile intermediate building blocks for the pharmaceutical, flavoring, and polymer industries. Previous research on alkene epoxidation has focused on the use of several oxidizing agents and/or different enzymes, including cytochrome P450 monooxygenases, as well as microbial whole-cell catalysts that have several drawbacks. Alternatively, we explored the ability of unspecific peroxygenases (UPOs) to selectively epoxidize terminal alkenes. UPOs are attractive biocatalysts because they are robust extracellular enzymes and only require H2O2 as cosubstrate. Here, we show how several UPOs, such as those from Cyclocybe (Agrocybe) aegerita (AaeUPO), Marasmius rotula (MroUPO), Coprinopsis cinerea (rCciUPO), Humicola insolens (rHinUPO), and Daldinia caldariorum (rDcaUPO), are able to catalyze the epoxidation of long-chain terminal alkenes (from C12:1 to C20:1) after an initial optimization of several reaction parameters (cosolvent, cosubstrate, and pH). In addition to terminal epoxides, alkenols and other hydroxylated derivatives of the alkenes were formed. Although all UPOs were able to convert and epoxidize the alkenes, notable differences were observed between them, with rCciUPO being responsible for the highest substrate turnover and MroUPO being the most selective with respect to terminal epoxidation. The potential of peroxygenases for epoxidizing long-chain terminal alkenes represents an interesting and green alternative to the existing synthesis technologies.